2008
DOI: 10.2746/042516408x333001
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of the severe combined immunodeficiency disease gene among horses in Morocco

Abstract: Severe combined immunodeficiency disease (SCID) of horses is an autosomal, recessive hereditary disease occurring among Arabian or crossbred Arabian horses. The genetic defect responsible was previously identified as a 5-base pair deletion in the gene encoding the catalytic subunit of the DNA dependant protein kinase (DNA-PKcs). This study was carried out to determine the frequency of SCID and identify horses carrying the gene for SCID among Arabian and Arabian crossbred stallions and mares in Morocco using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 4 publications
0
12
0
1
Order By: Relevance
“…Several previous genetic studies have investigated the five nucleotide deletion in the DNA-PKcs gene using primers that yield a PCR product of 521 bp [25], 259 bp [15], 235 bp [16], 179 bp [10], 174 bp [22], 169 bp [8,26], 163 bp [1,9,19,27], 162 bp [11], and 135 bp [13,17] in different Arabian horse populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous genetic studies have investigated the five nucleotide deletion in the DNA-PKcs gene using primers that yield a PCR product of 521 bp [25], 259 bp [15], 235 bp [16], 179 bp [10], 174 bp [22], 169 bp [8,26], 163 bp [1,9,19,27], 162 bp [11], and 135 bp [13,17] in different Arabian horse populations.…”
Section: Discussionmentioning
confidence: 99%
“…To detect wild and mutant SCID alleles, the amplified PCR products were electrophoresed on 10% [10], 8% [13,15], and 6% Polyacrylamide gel [8,27], 4% agarose gel [17], or capillary electrophoresis [9,11,16,19]. In addition to electrophoresis, sequencing analysis could be performed to identify the genotypes of a population in terms of the presence/absence of SCID mutant alleles, as in these studies [1,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After development of reliable and useful DNAbased tests, contemporary incidence values of SCID carrier and clinically affected foals have been increasingly reported from different countries (3,11,14,21,20,22,26). For example, it is reported that 17 of 204 (8.3%) foals are found SCID affected in Australia (11).…”
Section: Discussionmentioning
confidence: 99%
“…These include polymerase chain reaction analysis (3,14,26), polymerase chain reaction followed by southern hybridization analysis (17) and fragment and sequence analysis based on capillary electrophoresis (20). In this study, PCR followed by high-resolution agarose gel electrophoresis was chosen because of its user-friendly application and economical advantage (26).…”
Section: Discussionmentioning
confidence: 99%